Counseling with crossword puzzle games on knowledge about dental health maintenance in elementary school children - Lestari, Tina; Fadjeri, Indrayati; Emini, Emini (Journal Center of Excellent : Health Assistive Technology, 2026)
Background: Oral health is an essential component of overall health. Primary school-aged children are particularly vulnerable to dental problems due to limited knowledge and inadequate oral hygiene practices. Educational interventions using engaging methods, such as crossword puzzles, have been shown to be effective in enhancing children’s understanding of oral health. Objective: To the knowledge of oral health maintenance before and after an educational intervention using crossword puzzles among students of Class B, Grade V, at SDN Pondok Labu 14 Pagi, South Jakarta. Method: This study employed a pre-experimental design with a one-group pre-test and post-test approach. The sample consisted of 30 Grade VB students at SDN Pondok Labu 14 Pagi, South Jakarta, selected using total sampling. The data collection instrument was a questionnaire assessing knowledge of oral health maintenance, while the educational intervention was delivered using a crossword puzzle as the learning medium. Results: Knowledge of oral health maintenance before and after the educational intervention using crossword puzzles showed notable improvements. The proportion of students in the “good” category increased from 6.7% to 76.6%, while those in the “moderate” category decreased from 40% to 23%. Students in the “poor” category, initially 53.3%, were no longer observed after the intervention (0%). The mean knowledge score after the intervention was 86%, representing an increase of 33% compared to the pre-test. Conclusion: There was an increase in knowledge about dental health maintenance after counseling using crossword puzzles in elementary school children